SURVEY OF K-DRAMA CONSUMPTION TRENDS IN VIETNAM - Cao, Thi Hai Bac (VNU Journal of Foreign Studies, 2023)
Using the survey method of questionnaire, this study aims to investigate K-Drama consumption trends in Vietnam. Firstly, the frequent viewing rate of Korean Drama is over 50%. Secondly, the majority of Vietnamese audiences are willing to pay for copyright drama services as well as choose services with an internet connection rather than through channels on TV. Thirdly, drama’s content or script, melodrama are appreciated most by the respondents.